Laksamana Armada Zheng He : Syahbandar Agung Haji Muhammad Cheng Ho penabur benih perdamaian dan kerja sama internasional - Dirdjosisworo, Soedjono, 1940-; Mashudi, H. (Bandung : CV. Utomo, 2006)
Historical research on the Admiral Zheng He expedition and international relationship in Indonesia
Daftar pustaka : p. 126
Keywords: Cheng, Ho, -- 1371-1435; Explorers -- China -- Biography; Explorers -- China